การนำวิธีการต่อรองคำรับสารภาพมาใช้กับองค์กรอาชญากรรม - อรสุดา แสงก่ำ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This thesis is focused to study plea bargaining used in organized crime cases. This is due to the ratification of Thailand in the United Nations convention against transnational organized crime 2000, which has its prescribed measure provision in the article 26. Furthermore, to study legal measures for evidence searching whether they can be used effectively to impose the law against organized crime and the suitability in bringing plea bargaining measure to be used in Thailand, also whether Thailand has her domestic laws that are consistent with this Convention and the suitability in adapting U.S. laws within Thai context. According to the research, it found that special legal measures for evidence searching have not been used with organized crime effectively. There are problems of legal and practice, for the instance, the use of wiretapping because the performance of organized crime is covert and confidential. Their supreme boss would not allow them to use electronic equipment that can be traced, or even use secret code in their communication. As for the legal problem, it found that there is limitation to use special technique investigation tools only with some legal offenses, which are not covered many kinds of organized crime activities. Because of the condition of the problem concerning legal measures for evidence searching to impose law against organized crime, an author has an opinion that there should be another measure to get information from the accomplice in the organized crime which is the plea bargaining measure. I, therefore, recommend the augment of this measure in the Criminal Procedure Code. By doing this it will be in conforming to said convention and in this case, the U.S. laws should be considered as the model in improving Thai legislature accordingly.